The Deep Learning Quality and Pedagogical Competence on Academic Resilience: Kualitas Deep Learning dan Kompetensi Pedagogik terhadap Resiliensi Akademik - Bagja Riyanto; Sapoetro, Nico Tri Raharjo; Socrates, Teguh Putra; Aman, And (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Teachers’ pedagogical competence within the Merdeka Curriculum is essential for supporting meaningful and student-centered learning processes. Specific Background: In Social Studies education, deep learning requires active student engagement supported by structured pedagogical interaction, which relates to the development of academic resilience. Knowledge Gap: Prior studies have largely examined deep learning, pedagogical competence, and academic resilience separately, with limited integration of these variables, particularly in junior high school Social Studies contexts. Aims: This study aims to analyze the relationship between the quality of deep learning implementation and teachers’ pedagogical competence on students’ academic resilience at SMP Negeri 1 Semarang. Results: The findings reveal that both variables show positive and significant relationships with academic resilience, both partially and simultaneously, where resilience develops through active engagement in structured learning challenges supported by directed pedagogical interaction. Novelty: This study positions academic resilience not merely as an individual attribute but as a construct shaped through the interaction between cognitive demands of deep learning and pedagogical support within classroom practice. Implications: The study highlights the importance of designing cognitively challenging and well-structured learning activities, supported by constructive feedback, appropriate scaffolding, and a non-judgmental classroom environment to sustain student engagement and manage learning difficulties. Highlights• Structured learning challenges with guided interaction relate to student persistence• Teacher capability in classroom design and feedback supports adaptive learning responses• Combined classroom practices explain a measurable portion of resilience variation KeywordsDeep Learning; Pedagogical Competence; Academic Resilience; Social Studies Learning; Merdeka Curriculum